An Analytical Study on Sliding Mode Strength at the Bonded Interface Depending on the Inclined Angle of Unidirectional CFRP Inclined Double Cantilever with Laminated Structure - Park, Jae-Woong; Cho, Jae-Ung (International Journal of Engineering and Technology, 2018)
Background/Objectives: CFRP is getting a great deal of attention with its next-generation lightweight materials.Â Weight lightening can be greatly improved by designing the structure using the method of bonding lightweight materials.Methods/Statistical analysis: This study was based on BS (British standard) 7991 for mode II (Sliding mode).Â BS 7991 is a basic research method for identifying the basic elements of CZM(Cohesive zone method). In the mode II as sliding mode of the inclined double cantilever beam, the effects on the materials and the mechanical properties shall be identified when the sliding load working at the bonded interface appears.Findings: Unidirectional CFRP shall be designed in accordance with quasi-isotropic laminate in order for its elastic stiffness to be designed similarly at all the coordination directions. Therefore, the laminate structure used in this study was designed to be [0 / Â± 603]s. This is because the adhesion force acting on the bonded interface varies according to the progress of the failure when the interfacial failure occurs in the mode II as sliding mode of the inclined double cantilever. Quasi-isotropic laminate structure has an advantage of not setting differently elastic stiffness depending on the coordination in all the directions. The analysis condition of a restraint has been applied to one of the inclined double cantilevers with remote displacement excluding the rotation direction. The freedom of rotation direction along with forced displacement of sliding direction has been given to remote displacement in the other cantilever. Forced displacement speed was set at 3 mm/min. Given the free direction of rotation in both cantilevers, the inclined double cantilever has been ruptured, minimizing the interference between the elements.Improvements/Applications: In this research, a database for the application of lightweight materials and the bonding method, which are the design elements for lightweight structure has been constructed.Â Â